Mosque-Based Eco-Social Welfare: the Case of ‘Brigade Bersih Masjid’ Program in Sragen - Paraswati, Ramita; Rosyid, Muhammad (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
This study explores the role of Muslim scholars and community leaders in promoting environmental sustainability through mosque-based initiatives. Focusing on Al-Falah Mosque in Sragen, it examines the